Antioxidant defence-related genetic variants are not associated with higher risk of secondary thyroid cancer after treatment of malignancy in childhood or adolescence - Vodušek, Ana Lina (Radiology and oncology (Ljubljana), 2016)
Background. Thyroid cancer is one of the most common secondary cancers after treatment of malignancy in childhood or adolescence. Thyroid gland is very sensitive to the carcinogenic effect of ionizing radiation, especially in children. Imbalance between pro- and anti-oxidant factors may play a role in thyroid carcinogenesis. Our study aimed to assess the relationship between genetic variability of antioxidant defence-related genes and the risk of secondary thyroid cancer after treatment of malignancy in childhood or adolescence. Patients and methods. In a retrospective study, we compared patients with childhood or adolescence primary malignancy between 1960 and 2006 that developed a secondary thyroid cancer (cases) with patients (controls), with the same primary malignancy but did not develop any secondary cancer. They were matched for age, gender, primary diagnosis and treatment (especially radiotherapy) of primary malignancy. They were all genotyped for SOD2 p.Ala16Val, CAT c.-262C>T, GPX1 p.Pro200Leu, GSTP1 p.Ile105Val, GSTP1 p.Ala114Val and GSTM1 and GSTT1 deletions. The influence of polymorphisms on occurrence of secondary cancer was examined by McNemar test and Cox proportional hazards model. Results. Between 1960 and 2006 a total of 2641 patients were diagnosed with primary malignancy before the age of 21 years in Slovenia. Among them 155 developed a secondary cancer, 28 of which were secondary thyroid cancers. No significant differences in the genotype frequency distribution were observed between cases and controls. Additionally we observed no significant influence of investigated polymorphisms on time to the development of secondary thyroid cancer. Conclusions. We observed no association of polymorphisms in antioxidant genes with the risk for secondary thyroid cancer after treatment of malignancy in childhood or adolescence. However, thyroid cancer is one of the most common secondary cancers in patients treated for malignancy in childhood or adolescence and the lifelong follow up of these patients is of utmost importance.
Keywords: antioksidativni geni; antioxidant genes; genetic polymorphism; genski polimorfizem; secondary thyroid cancer; sekundarni rak ščitnice